2009
DOI: 10.1210/jc.2008-0323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Exon 3-Deleted/Full-Length Growth Hormone (GH) Receptor Polymorphism on the Response to GH Replacement Therapy in Adults with Severe GH Deficiency

Abstract: The presence of d3-GHR allele did not influence the response to GH replacement therapy in our cohort of adults with severe GHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
0
24
1
2
Order By: Relevance
“…Therapeutic outcomes examined in this study were changes on serum IGF-I levels and total body fat mass during therapy. In contrast to the previous study, we did not find any influence of d3-GHR in those parameters, neither at baseline nor in response to rhGH therapy (45). We believe, however, that our unique large short-term therapeutic response study (1 week) is a more optimal model for the purpose of better understanding the impact of the GHR genotype on GH sensitivity as long-term studies are more subjected to confounders such as dose titration and adherence to the treatment.…”
Section: Ghr Polymorphism In Adults With Growth Hormone Deficiency (Ghd)contrasting
confidence: 99%
“…Therapeutic outcomes examined in this study were changes on serum IGF-I levels and total body fat mass during therapy. In contrast to the previous study, we did not find any influence of d3-GHR in those parameters, neither at baseline nor in response to rhGH therapy (45). We believe, however, that our unique large short-term therapeutic response study (1 week) is a more optimal model for the purpose of better understanding the impact of the GHR genotype on GH sensitivity as long-term studies are more subjected to confounders such as dose titration and adherence to the treatment.…”
Section: Ghr Polymorphism In Adults With Growth Hormone Deficiency (Ghd)contrasting
confidence: 99%
“…Another study showed that d3-GHR carriers require w25% less GH during replacement therapy than fl-GHR carriers (10). Other studies have, however, not shown associations between d3/fl genotype and response to GH in adults (8,9). …”
Section: Discussionmentioning
confidence: 99%
“…Studies on adult GHD populations have produced more conflicting data, showing either no association or a better response in carriers of the d3-GHR (8,9,10,11). Previous studies have, however, focused on the long-term (O6 months) response to GH replacement therapy, rather than the early response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in GHD adults have found an association between the response to GH and clinical and biochemical parameters, such as body mass index (BMI), age, gender, serum GH-binding protein (GHBP) levels, GH dose, and the route of estrogen replacement in women (2,(11)(12)(13)(14)(15)(16). More recently, a genetic predictor, the GH receptor (GHR) polymorphism, has been studied in both children and adults with GHD, showing only a weak influence on the clinical response to GH therapy (17)(18)(19) or no influence at all (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%